Recruitment of south Asian carers into a survey-based research study. (April 2021) - Fry, Gary; Gilgallon, Kathryn; Khan, Wajid; Reynolds, Damian; Spencer, Graham; Wright, Alice; Parveen, Sahdia
Because of challenges involved in recruitment, little research has focused on care needs of minority ethnic groups. This article reports on a study that recruited 186 British south Asian carers of people with dementia. Four obstacles were faced: language barriers, confusion over research, feelings of shame/stigma, and mistrust. Researchers drew on various methods: enlisting multilingual researchers; activating contacts in minority ethnic communities; engaging with community groups; emphasising potential for enhancing support services; and tailoring research instruments to minority ethnic issues. Tips are offered to other researchers recruiting minority ethnic participants into studies.